1977
DOI: 10.1159/000176077
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of <sup>14</sup>C-Linoleic Acid by the Rat Fetus

Abstract: Following ingestion, by the 20-day pregnant mother, of (1-14C)linoleic acid, the retention and distribution of ‘4C are determined in the fetus, placenta and mother, after 1, 3 and 6 h. Comparison of the specific activities of linoleic and arachidonic acids in the maternal plasma, liver and placenta, and the fetal plasma, liver and carcass leads to the conclusion of a selective materno-fetal transfer of arachidonic acid, relative to linoleic acid, through the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Apparently, these sequences of metabolic events involved in the synthesis of arachidonic acid are limited by the in vivo activity of A6-desaturase, since the desaturation of linoleic to 71inolenic acid is a rate-limiting step in the conversion of linoleic to arachidonic acid (2). Following the ingestion of [ 1-14C] linoleic acid by pregnant rats, Pascaud et al (3,4) demonstrated that: 1) fetal arachidonic acid is originated essentially iW the maternal liver, and 2) this acid is selectively transferred from mother to fetus through the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, these sequences of metabolic events involved in the synthesis of arachidonic acid are limited by the in vivo activity of A6-desaturase, since the desaturation of linoleic to 71inolenic acid is a rate-limiting step in the conversion of linoleic to arachidonic acid (2). Following the ingestion of [ 1-14C] linoleic acid by pregnant rats, Pascaud et al (3,4) demonstrated that: 1) fetal arachidonic acid is originated essentially iW the maternal liver, and 2) this acid is selectively transferred from mother to fetus through the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the maternal blood in the supply of w6 polyunsaturated fatty acids to the fetus [6], suggested by in vitro investi gations on the rat fetoplacental unit [9], has been demonstrated in our laboratory by in vivo isotopic experiments to be reported elsewhere.…”
mentioning
confidence: 99%